2021
DOI: 10.1155/2021/8855536
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Chemical Components and Gastrointestinal Function on Rats of the Raw Product and Licorice-Simmered Product of Polygala tenuifolia

Abstract: The root of Polygala tenuifolia Willd. (Polygalaceae) (PT) has been listed as a nootropic, anti-inflammatory, and antipsychotic medicine that can cure insomnia. Raw PT (RPT) is toxic and must be processed before clinical use. Licorice-simmered PT (LPT) is one of the most common processed products. We conducted this study in order to investigate the differences in chemical components and gastrointestinal function between RPT and LPT. We used principal component analysis (PCA) and quantitative analysis to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…GAS is one of the brain–gut peptides, synthesized mainly by G cells distributed in the gastrointestinal mucosa. It is known that GAS and MTL can promote gastric acid and pepsin secretion, stimulate gastrointestinal peristalsis, and promote gastric emptying . In this study, there were significant differences in the gastrointestinal function-related proteins GAS and MTL between the model and the normal group, suggesting that gastrointestinal dysfunctions occurred in both constipation and depression.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…GAS is one of the brain–gut peptides, synthesized mainly by G cells distributed in the gastrointestinal mucosa. It is known that GAS and MTL can promote gastric acid and pepsin secretion, stimulate gastrointestinal peristalsis, and promote gastric emptying . In this study, there were significant differences in the gastrointestinal function-related proteins GAS and MTL between the model and the normal group, suggesting that gastrointestinal dysfunctions occurred in both constipation and depression.…”
Section: Discussionmentioning
confidence: 63%
“…It is known that GAS and MTL can promote gastric acid and pepsin secretion, stimulate gastrointestinal peristalsis, and promote gastric emptying. 21 In this study, there were significant differences in the gastrointestinal function-related proteins GAS and MTL between the model and the normal group, suggesting that gastrointestinal dysfunctions occurred in both constipation and depression. Further, we speculate that gastrointestinal dysfunctions of constipation and depression could accelerate the occurrences and/or the development of each other.…”
Section: Correlation Of Gastrointestinal Functions Between Constipati...mentioning
confidence: 54%
“…1,2 However, previous research has highlighted the severe gastrointestinal toxicity associated with PT, leading to gastrointestinal motility disorders, mucosal damage, and even death in mice. [3][4][5] Additionally, saponins have been identified as the primary toxic components of PT, significantly hampering its application and development. [6][7][8] Magnolia Officinalis Cortex (Magnolia Officinalis Rehd.et Wils, MO, Hou po in Chinese) has been extensively used in Asia for approximately 2000 years, primarily for the treatment of gastrointestinal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,5-Trimethoxycinnamic acid (C 12 H 14 O 5 , TMCA; CAS 90-50-6; molar mass 238.24 g mol –1 ; Figure ) is one of the active components of traditional Chinese medicine Yuanzhi. Previous literature reports have found that TMCA and its derivatives have important medical effects and are widely used in sleep disorders, depression, toxicity reduction, and other aspects, with good bioavailability. , Meanwhile, TMCA could generate antiseizure effects by combining with the GABAA (gamma-aminobutyric acid type A) receptor complex, which was utilized to exploit therapeutic agents for anxiety depression and therapeutic agents against morphine dependence . In addition, some derivatives synthesized with TMCA , showed good anticonvulsant activity and sedative effect, which was used for the development of anticonvulsant drugs and sedatives .…”
Section: Introductionmentioning
confidence: 99%